Effect of increasing radiation dose on pathologic complete response in rectal cancer patients treated with neoadjuvant chemoradiation therapy. (1st December 2016) - Hall, Matthew D.; Schultheiss, Timothy E.; Smith, David D.; Fakih, Marwan G.; Wong, Jeffrey Y.C.; Chen, Yi-Jen
Abstract: Background: Neoadjuvant chemoradiation therapy (CRT) increases pathological complete response (pCR) rates compared to radiotherapy alone in patients with stage II-III rectal cancer. Limited evidence addresses whether radiotherapy dose escalation further improves pCR rates. Our purpose is to measure the effects of radiotherapy dose and other factors on post-therapy pathologic tumor (ypT) and nodal stage in rectal cancer patients treated with neoadjuvant CRT followed by mesorectal excision. Material and methods: A non-randomized comparative effectiveness analysis was performed of rectal cancer patients treated in 2000–2013 from the National Oncology Data Alliance™ (NODA), a pooled database of cancer registries from >150 US hospitals. The NODA contains the same data submitted to state cancer registries and SEER combined with validated radiotherapy and chemotherapy records. Eligible patients were treated with neoadjuvant CRT followed by proctectomy and had complete data on treatment start dates, radiotherapy dose, clinical tumor (cT) and ypT stage, and number of positive nodes at surgery (n = 3298 patients). Multivariable logistic regression was used to assess the predictive value of independent variables on achieving a pCR. Results: On multivariable regression, radiotherapy dose, cT stage, and time interval between CRT and surgery were significant predictors of achieving a pCR. After adjusting for the effect of other variates, patients treated with higher radiotherapy doses were also more likely to have negative nodes at surgery and be downstaged from cT3-T4 and/or node positive disease to ypT0-T2N0 after neoadjuvant CRT. Conclusion: Our study suggests that increasing dose significantly improved pCR rates and downstaging in rectal cancer patients treated with neoadjuvant CRT followed by surgery.